2019
DOI: 10.1186/s40575-019-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma-causing ADAMTS17 mutations are also reproducibly associated with height in two domestic dog breeds: selection for short stature may have contributed to increased prevalence of glaucoma

Abstract: Background In humans, ADAMTS17 mutations are known to cause Weill-Marchesani-like syndrome, which is characterised by lenticular myopia, ectopia lentis, glaucoma, spherophakia, and short stature. Breed-specific homozygous mutations in ADAMTS17 are associated with primary open angle glaucoma (POAG) in several dog breeds, including the Petit Basset Griffon Vendeen (PBGV) and Shar Pei (SP). We hypothesised that these mutations are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…However, overexpression of FGF4 associated with insertion of FGF4 retrogenes on CFA12 and CFA18 appear to have broader influences on limb length across many breeds and are the only genes to have been implicated in body size in across-breed association studies ( 3 , 13 16 ). While many breed specific mutations are considered undesirable ( 8 10 , 12 ) some of these genes have been under positive selection in specific breeds due to their effects on height, despite associated pathologies including glaucoma and IVDD ( 11 , 13 ).…”
Section: “Short Limbed” Dogs and Ivddmentioning
confidence: 99%
“…However, overexpression of FGF4 associated with insertion of FGF4 retrogenes on CFA12 and CFA18 appear to have broader influences on limb length across many breeds and are the only genes to have been implicated in body size in across-breed association studies ( 3 , 13 16 ). While many breed specific mutations are considered undesirable ( 8 10 , 12 ) some of these genes have been under positive selection in specific breeds due to their effects on height, despite associated pathologies including glaucoma and IVDD ( 11 , 13 ).…”
Section: “Short Limbed” Dogs and Ivddmentioning
confidence: 99%
“…While proof still needs to be provided in dogs that tissue biomechanical properties are linked to IOP susceptibility, initial studies in ADAMTS10 ‐mutant Beagles with OAG showed that their posterior sclera is weaker with reduced fibrous collagen density, possibly explaining the slower optic nerve degeneration with chronic, severe IOP increases compared to dogs of other breeds 45,229‐231 . Similar findings can be expected in other ADAMTS10 ‐ and ADAMTS17 ‐mutant dogs with OAG, for example Norwegian Elkhound ( ADAMTS10 ), 36 Petit Basset Griffon Vendéen ( ADAMTS17 ), 38,232 Basset Fauve de Bretagne ( ADAMTS17 ), 40 and Chinese Shar‐Pei ( ADAMTS17 ) 41,232 . Some transgenic mice are also resistant to glaucomatous damage, while hardening of the sclera with cross‐linking agents worsens IOP‐related damage to the RGC axons 224 …”
Section: Influencing the Biomechanical Properties Of The Eyementioning
confidence: 71%
“…Since then, at least 15 genes have been observed to be altered in both PRA and RP (Online Mendelian Database, OMIA, https://omia.org/; RetNet, https://sph.uth.edu/RetNet/). A similar pattern can be further recognized for glaucoma and ectopia lentis (EL), a canine equivalent of lens luxation (LL): ADAM metallopeptidase with thrombospondin type 1 motif-proteins -ADAMTS10 and ADAMTS17 -genes have been observed to harbor variants causative for primary glaucoma and LL in dogs and syndromic diseases, with symptoms including glaucoma and EL, in humans (Weill-Marchessani syndrome) (Farias et al, 2010;Forman et al, 2015;Jeanes et al, 2019;Morales et al, 2009). Overall, this pattern of shared genes harboring eye disease-causing variants indicates a need for further research in both species.…”
Section: Introductionmentioning
confidence: 77%